2014
DOI: 10.1084/jem.20131092
|View full text |Cite
|
Sign up to set email alerts
|

β2 integrin mediates hantavirus-induced release of neutrophil extracellular traps

Abstract: β2 Integrin–mediated systemic release of neutrophil extracellular traps is a novel mechanism of immunopathology associated with hantavirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(160 citation statements)
references
References 72 publications
4
150
0
6
Order By: Relevance
“…NETs contribute to host defense by trapping microorganisms and limiting their spread, and by serving as a scaffold for thrombus formation on endothelium. However, excess NET formation (or impaired NET clearance) can lead to tissue damage and coagulopathies, and has been implicated in the pathogenesis of highly inflammatory conditions (e.g., sepsis) and other viral hemorrhagic fevers (Kaplan and Radic, 2012; Raftery et al, 2014). Consistent with the possibility of NET formation in EVD, core histone proteins (e.g., HIST3H2BB), and azurophilic granule proteins (MPO, CTSG, PRTN3, and AZU1) are present in the plasma of EVD patients but not that of healthy individuals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NETs contribute to host defense by trapping microorganisms and limiting their spread, and by serving as a scaffold for thrombus formation on endothelium. However, excess NET formation (or impaired NET clearance) can lead to tissue damage and coagulopathies, and has been implicated in the pathogenesis of highly inflammatory conditions (e.g., sepsis) and other viral hemorrhagic fevers (Kaplan and Radic, 2012; Raftery et al, 2014). Consistent with the possibility of NET formation in EVD, core histone proteins (e.g., HIST3H2BB), and azurophilic granule proteins (MPO, CTSG, PRTN3, and AZU1) are present in the plasma of EVD patients but not that of healthy individuals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that neutrophils are capable of recognizing IAV and IAV-infected cells (91)(92)(93)(94), although discrepancies in data suggest that neutrophil responses to IAV are dependent on the viral strain (92)(93)(94)(95). Interest in the role of neutrophils in viral disease is quickly growing (56,(96)(97)(98), and the topic deserves further research.…”
Section: Discussionmentioning
confidence: 99%
“…Cell susceptibility to hantavirus, however, depends not only on the expression of ITB3 [9, 10]; other cellular factors, such as decay-accelerating factor (DAF1) and the receptor of complement C1q are also important in hantavirus entry [1114]. In addition, integrin β2 was recently identified as a receptor for HTNV and as responsible for hantavirus pathogenesis [15]. The precise roles of each of these factors in hantavirus cell entry are currently unclear, however.…”
Section: Introductionmentioning
confidence: 99%